Job Satisfaction in the Health Care Sector: Empirical Evidence from Medical Care in Greece - Gkliati, Alexandra; Saiti, Anna (European Journal of Economics and Business Studies, 2023)
It is extremely important for employees in every sector of an economy to be satisfied with their work since job satisfaction contributes significantly to improvements in their productiveness and performance. This paper deals with the very sensitive sector of health care in which medical staff provide citizens with health care services. The job satisfaction of these medical care providers is of particular importance when aiming to improve the quality of their services. Literature on job satisfaction among the providers of medical care is limited since researches have focused mainly on users’ satisfaction with the medical care services provided. In an era in which many countries worldwide are facing uncertainty and the social insurance systems are confronted with serious problems as they strive to respond to a number of changes, the Greek health care sector is no exception. With particular reference to the Greek reality, due to the heavy recession that the country has been facing for a number of years, health care expenditures have been cut dramatically and, as a result, the working conditions in public hospitals have been negatively influenced. Based on the above, the purpose of this paper is, through empirical investigation, to examine the levels of job satisfaction among Greek doctors who work in public hospitals and to determine the factors that may influence the satisfaction they gain from their work.